A super-resilient and highly sensitive graphene oxide/cellulose-derived carbon aerogel. Issue 35 (1st September 2020) - Jiang, Wenzhao; Yao, Chenfei; Chen, Wei; Li, Di; Zhong, Linxin; Liu, Chuanfu
Abstract : By engineering an ordered lamellar texture and stabilizing the structure during carbonization, an ultralight carbon aerogel with superior mechanical performances and high linear sensitivity is successfully fabricated. Abstract : Ultralight and resilient carbon aerogels with high compressibility and fatigue resistance are of great interest in various applications, such as wearable pressure-sensing electronics and flexible energy storage systems. However, owing to the irrational structural design and uncontrollable carbonization process, fabricating carbon aerogels with both high mechanical performances and linear sensitivity from green biopolymers remains a great challenge. Herein, by engineering an ordered lamellar texture and stabilizing the structure during carbonization, an ultralight carbon aerogel (8.16 mg cm −3 ) with superior mechanical performances and high linear sensitivity is successfully fabricated from graphene oxide and water-soluble cellulose. The ordered, continuous, and waved-shaped lamellar architecture can efficiently transfer stress throughout the microstructure and thus endows the carbon aerogel with exceptionally high compressibility, resilience and structural stability. The as-prepared carbon aerogel maintains high resilience for more than 300 cycles under extremely high compression strain (99%). It also displays an ultrahigh linear sensitivity (15.8 kPa −1 ) in a wide pressure range (0–18 kPa), which enables it to detect tiny changes in human biosignals, exhibiting promising application in wearable electronics.